Discomycetes of Kharkiv Forest-Steppe (Ukraine): the annotated checklist (CHORNOMORSKI BOTANICAL JOURNAL, 2017)
The modern data on the discomycetes diversity of Kharkiv Forest-Steppe are summarized. The checklist is based on the analysis of literature data starting from the middle XIX century, critical revision of materials from scientific herbarium CWU Myc and own studies performed in 2010-2017 . The list includes 254 species of discomycetes belonging to 115 genera, 35 families, 8 orders and 5 classes of Ascomycota. Among them 134 species are new to Kharkiv Forest-Steppe, 43 are new to Left Bank Ukraine and 36 species are first time reported to Ukraine.
Keywords: Ascomycota, biodiversity, floristic novelties, abundance.